English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-05 12:48:31 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

f(g(x))= 4g(x) -5
= 4(x/3) -5
= 4x/3 -5
s

2006-11-05 12:52:06 · answer #1 · answered by Anonymous · 0 1

f(g(x))=f(x/3)=(4/3)x-5

2006-11-05 20:52:51 · answer #2 · answered by yupchagee 7 · 1 0

4(x/3)-5



(4x/12)-5


x/3 - 5

2006-11-05 20:50:45 · answer #3 · answered by Anonymous · 1 1

f(g(x)) = (4x/3)-5


Doug

2006-11-05 20:53:00 · answer #4 · answered by doug_donaghue 7 · 0 0

They all beat me!

2006-11-05 20:57:30 · answer #5 · answered by MollyMAM 6 · 0 0

fedest.com, questions and answers